Daniel hauer's attitudes towards Vietnamese english teachers’ pronunciation represented on youtube and Vietnamese english speakers’ responses to them = Quan điểm của Daniel Hauer về phát âm tiếng anh của giáo viên Việt Nam và phản hồi của người Việt nói Tiếng anh về quan điểm đó - Hoàng, Thị Hải Yến (2021)
English is now regarded as an international language (EIL) with many distinctive varieties; however, there remain diverse attitudes towards these varieties, including their pronunciation. This research investigated the case of Daniel Hauer, an American English teacher in Vietnam, who has recently stirred up debates over standard pronunciation with his videos “When Americans listen to English of Vietnamese people” and “Dirty competition?”. The researcher applied a critical intercultural analysis to figure out what Hauer’s attitudes towards English pronunciation were and how Vietnamese English learners responded to them through their comments on the video. Results showed that despite his claims of a fair test, Hauer seemed to prioritize his native English variety when adopting methodology and employing testers to assess Vietnamese English teachers’ pronunciation. This reflected his position in the Minimization stage of ethnocentrism. Meanwhile, in response to Hauer’s arguments, Vietnamese learners showed their overgeneralization, stereotypes and prejudice against their own ingroup members, indicating cultural cringe in their ideology. In some cases, these perceptions of Vietnamese learners were seen to be impinged by Daniel Hauer’s opinions on the matter. These views revealed an agreement in setting native pronunciation standards for Vietnamese English learners, which resisted the commonly accepted attitudes towards English varieties in EIL context